Antibiotic resistance of bacteria isolated in blood and urine cultures in hospitalized children. Almanzor Aguinaga Asenjo National Hospital 2017 - 2018 - Sosa-Campos, Jessica Milagros (2021)
Introduction: Antimicrobial resistance increases morbidity and mortality and is a serious problem in the world. Objective: to describe the antibiotic resistance of bacteria isolated in blood and urine cultures in hospitalized children under 15 years of age. Material and Methods: Descriptive - retrospective study. Bacterial identification was made with VITEK XL, antibiotic susceptibility with CLSI. Results: Blood cultures: Staphylococcus hominis 12.5% ​​resistant to Vancomycin. Staphylococcus epidermidis had 100% resistance to Oxacillin and 0% resistance to Vancomycin. Urine cultures: Klebsiella pneumoniae 0% resistance to Amikacin, Gentamicin and Nitrofurantoin. Escherichia Coli, had resistance to Amikacin 1.96%, Nitrofurantoin 3.92%. Conclusions: E, Coli, resistance less than 6.25% for Amikacin and Nitrofurantoin. Klebsiella pneumoniae, 0% resistance for Amikacin and Gentamicin. Blood cultures: Staphylococcus epidermidis, zero resistance to Vancomycin. Staphylococcus hominis, resistance less than 12% for Vancomycin and Rifampicin.